Anti-Toxoplasma gondii screening of MMV pandemic response box and evaluation of RWJ-67657 efficacy in chronically infected mice - Bruna Ramos dos Santos; Amanda Bruno da Silva Bellini Ramos; Renata Priscila Barros de Menezes; Marcus Tullius Scotti; Fábio Antônio Colombo; Marcos José Marques; Juliana Quero Reimão (Parasitology, 2023)
Toxoplasmosis is a significant public health concern with limited therapeutic options. The medicines for malaria venture (MMV) developed the pandemic response box (PRB) containing 400 drug-like molecules with broad pathogen activity. The aim of this work is to evaluate PRB compounds for their anti-Toxoplasma gondii activity and identify promising candidates for further evaluation. Screening identified 42 selective compounds with half effective concentration (EC50) ranging from 2.4 to 913.1 nm and half cytotoxic concentration (CC50) ranging from 6 μm to >50 μm. Selectivity index (SI) values (CC50/EC50) ranged from 11 to 17 708. Based on its in silico and in vitro profile and its commercial availability, RWJ-67657 was selected for further studies. Molecular docking analysis showed RWJ-67657 is predicted to bind to T. gondii p38 mitogen-activated protein kinase (TgMAPK). Oral administration of RWJ-67657 (20 mg kg day−1/10 days) significantly reduced parasite burden in chronically infected mice compared to mock-treated group (P < 0.01). These findings highlight the PRB as a promising source for anti-T. gondii compounds, with several showing favourable drug properties, including MMV1634492, MMV002731, MMV1634491, MMV1581551, MMV011565, MMV1581558, MMV1578577, MMV233495 and MMV1580482, firstly described here as anti-T. gondii agents. RWJ-67657 emerges as a valuable drug candidate for experimental chronic cerebral toxoplasmosis therapy.